UNIMAS FOOD STALL MANAGEMENT SYSTEM - NALINA NARAYANI, SIVAPRESAAD (Universiti Malaysia Sarawak (UNIMAS), 2019)
UNIMAS Food Stall Management System (UFMS) is an inventory management system that will be used by the food stall owner and the staffs. This system helps the food stall owner in terms of managing the staffs’ details, sales report and the inventories through online. Currently, the process of recording the reports and managing the inventories are done manually by using paper-based system. The downside of this system is that records tend to go missing because it was written and filed, and the file can be misplaced or damaged. Apart from that, another problem encountered by the food stall owner and staffs by using the traditional method is, they are not notified when the items are out of stock. By proposing this automated system, it can help the food stall owner to manage the staffs’ details, sales report and inventories more efficiently through a new computerized web-based system. The methodology that was used to develop this proposed system is Rapid Application Development (RAD) methodology.